PENGARUH KETERBUKAAN EKONOMI, CADANGAN VALAS, INFLASI DAN KURS TERHADAP CADANGAN DEVISA DAN PERTUMBUHAN EKONOMI INDONESIA - Vitriyanti, Made Aprilia; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Foreign exchange reserves are used as a measure of the strength and weakness of a country's economic fundamentals and economic growth is an important indicator in measuring the success of a country's economic development. The purpose are analysis ; 1) effect economic openness, foreign exchange reserves, inflation and the exchange rate on Indonesia's foreign exchange reserves, 2) effect economic openness, foreign exchange reserves, inflation and exchange rates on Indonesia's economic growth, 3) indirect effect economic openness, foreign exchange reserves, inflation, and exchange rates on economic growth through Indonesia's foreign exchange reserves. The data used secondary data, analysis technique used path analysis. The results is economic openness and exchange rates have positive effect, inflation has negative insignificant effect, foreign currency reserves have positive significant on the country's foreign exchange reserves. Economic openness, foreign exchange reserves, inflation, and foreign exchange reserves have a positive effect, exchange rates have negative significant effect on Indonesia's economic growth. I ndirectly the country's foreign exchange reserves mediate effect of economic openness and foreign exchange reserves but do not mediate the effect of inflation and exchange rates on Indonesia's economic growth.   Keywords: economic openness, foreign exchange reserves, inflation, exchange rates, foreign exchange reserves,economic growth